2018
DOI: 10.15642/jiis.2018.12.1.45-68
|View full text |Cite
|
Sign up to set email alerts
|

TOWARDS A RELIGIOUSLY HYBRID IDENTITY? The Changing Face of Javanese Islam

Abstract: This article seeks to revisit the discussion of Javanese Islam from an alternative point of view. It argues that the presentation of Javanese Islam in the previous studies is no longer adequate to accommodate the most current transformation of Javanese Islam. The identity of Javanese Islam can neither be seen from syncretic point of view nor normative perspective per se, since the identity of Javanese Islam has transformed itself into something different from the past. Becoming an abangan or santri in the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Kejawen tradition is a Javanese life guide that contains a philosophy of life, shared collective knowledge, and universal teachings of goodness embraced by the Javanese people (Hilmy, 2018;Muttaqin, 2014). Kejawen differs from a relatively religious abangan compared to abangan that tends to syncretism (Askuri & Kuipers, 2019;Geertz, 1983;M.…”
Section: Resultsmentioning
confidence: 99%
“…Kejawen tradition is a Javanese life guide that contains a philosophy of life, shared collective knowledge, and universal teachings of goodness embraced by the Javanese people (Hilmy, 2018;Muttaqin, 2014). Kejawen differs from a relatively religious abangan compared to abangan that tends to syncretism (Askuri & Kuipers, 2019;Geertz, 1983;M.…”
Section: Resultsmentioning
confidence: 99%
“…One can accept local traditions as long as they do not conflict with Islamic teaching s (Suciati and Erzard, 2018: 53). This is a form of Indonesian Is l amic society that has experienced improvement through acculturation and depth of religious understanding (Hilmy, 2018: 67, Burhan i , 2017. Understanding theology that is applicable in the life of Islamic society is the main need, as well as criticism of classical theology (Qomar, 2015: 223).…”
Section: Resultsmentioning
confidence: 99%
“…Both kejawen and Muslim groups continue to hold various rituals on a grander scale and perform new rituals that attract public attention, such as performing cultural rituals (Hudayana, 2021 ). Another study in Java has closely observed the shift in identity from abangan to Muslim (Hilmy, 2018 ; Natsir & Jinan, 2018 ). This identity has shifted due to higher literacy on Islamic teachings among Javanese Islamic communities; thus, they have begun to adopt more Islamic rituals and belief systems (Hilmy, 2018 ; Natsir & Jinan, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 86%
“…Another study in Java has closely observed the shift in identity from abangan to Muslim (Hilmy, 2018 ; Natsir & Jinan, 2018 ). This identity has shifted due to higher literacy on Islamic teachings among Javanese Islamic communities; thus, they have begun to adopt more Islamic rituals and belief systems (Hilmy, 2018 ; Natsir & Jinan, 2018 ). Muslim identity is increasingly accepted in Indonesian society and is presented as a popular identity that provides essential meaning in improving one’s socio-economic class status.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation